Sistem Diagnosa Penyakit THT Pada Balita Menggunakan Dempster Shafer - Maura Widyaningsih (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2018)
Computer field supports the existence of auxiliary program in medical development that is expert knowledge-based system, this system is one branch of Artifical Intellegence (AI). Expert systems are knowledge in learning about estimation or decision-making ability of an expert. Problem solving in the identification of a disease by using auxiliary program is needed a method and concept. Calculation techniques in computing systems are so important, given the level of need for information and the settlement of cases quickly.The results of the study are expert applications that assist in providing results of diagnosis of symptoms managed the system, with inference using forward chaining, and reasioning with Dempster Shafer. Dempster Shafer's method is not monotonous in solving uncertainty problems, due to the addition or subtraction of new facts. Rule changes will occur, allowing the system to do the work of an expert.Data changes will occur both to diseases, symptoms, solutions and rules, allowing the system to do the work of an expert. The results of manual calculations with the system gives results in accordance with the application of Dempster Shafer method. Management of rules in the database facilitates the search for symptoms within the system.